Improvement of carboxymethyl cellulase production from Chaetomium cellulolyticum NRRL 18756 by mutation and optimization of solid state fermenttion - Fawzi, Eman M; Hamdy, Hossam S (Bangladesh Journal of Botany, 2012)
Cellulase producing fungus Chaetomium cellulolyticum NRRL 18756 was subjected to various doses of gamma irradiation to enhance the production of the industrially important enzyme carboxymethyl cellulase (CMCase). Among all the mutants tested, M-7 obtained through 0.5 KGy irradiation showed highest extracellular CMCase production which is 1.6-fold higher than that of the wild type. Optimal conditions for the production of CMCase by the mutant fungal strain using solid-state fermentation were examined. The optimized medium consisted of sugarcane bagasse supplemented with 1% (w/w) peptone, 2.5mM MgSO4, and 0.05% (v/w) Tween 80. Optimal moisture content and initial pH was 40% (v/w) and 5.0-6.5, respectively. The medium was fermented at 40° C for 4 days. The resulting CMCase yield was 4.0-fold more than that of the wild type strain grown on the basal wheat bran medium. Some characteristics of partially purified CMCase from the mutant and wild type of C. cellulolyticum were investigated. The partially purified mutant CMCase was more stable than the wild type CMCase. Thus, the higher thermostability of mutant CMCase makes it a potential candidate for commercial and industrial process. Key words: Chaetomium cellulolyticum; Carboxymethyl cellulase; Mutation; Optimization; Solid state fermentation DOI: http://dx.doi.org/10.3329/bjb.v40i2.9769 Bangladesh J. Bot. 40(2): 139-147, 2011 (December)